An analysis of the mobility hub concept in the Netherlands: Historical lessons for its implementation. (October 2022) - Rongen, Tibor; Tillema, Taede; Arts, Jos; Alonso-González, María J.; Witte, Jan-Jelle
Abstract: The mobility hub concept has become increasingly popular within international research and policies, including in The Netherlands. However, judging by the (still) limited share of multimodality in the Netherlands, similar historical concepts seemed insufficient to prompting a fundamental shift from individual car use to multimodal transport. To enable planners to be better positioned to implement the mobility hub concept, we compared its value with that of related concepts that were previously implemented. Specifically, we examined historical Dutch policy documents and conducted expert and frontrunner interviews to evaluate the mobility hub as a policy concept. We first traced the evolution of the mobility hub, focusing on node and place-based concepts that have been implemented since the second half of the 20th century. We found that related concepts, such as Park and Ride (P + R) or transit-oriented development (TOD), have typically focused on improving transfers between collective and feeder transport, while interactions with land use have gained increased attention. We derived policy lessons from the implementation of these historical policy concepts. Our findings suggest that strategically chosen locations, integrated mobility systems, flanking policies, multi-level policy coherence and public–private cooperation are important considerations when implementing mobility hubs. Moreover, shared mobility, mobility as a service, vehicle electrification, and demand-responsive transit could advance the implementation of TOD, P + R, neighbourhood and rural hubs. In conclusion, the design of different types of mobility hubs should ideally be based on underlying policy objectives and adapted according to context. Highlights: Historical policies on mobility hubs resulted only in a limited shift towards multimodality. The TOD and P + R hubs are the predominant historical types combining interacting node and place characteristics. The design of mobility hubs should ideally be based on underlying policy objectives and adapted according to context. Historical lessons include strategically chosen locations, integrated mobility systems, flanking policies, multilevel policy coherence and public-private cooperation. Shared mobility, MaaS, vehicle electrification, and DRT may enable new hub types, such as neighbourhood and rural hubs.